The Connotations of CTs in Hawthorne's The Scarlet Letter: A Pragmatic Perspective - Hadeed, Safa Mawlood; Hadeed, Safa Mawlood; Hussein, Juma'a Qadir (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the connotations of colour terms in Nathaniel Hawthorne's The Scarlet Letter from viewpoint of pragmatics. As connotations of words, in general, and CTs, in particular, are context-based, pragmatics implicates assumptions suitable for the interpretation of the connotations of colour terms in The Scarlet Letter, and how Hawthorne used them in expressing their pragmatic meaning. In this regard, a qualitative analysis is used depending on Allan's (2007) proposition that connotations are pragmatic effect and not semantic. Considering the types of connotations in terms of their function, negative or positive attitude the study will adopt Allan's (2009) concept of X-phemism with its types-dysphemistic, orthophemistic, and euphemistic. All colour terms, basic and secondary, used in the novel: black, white, grey, red, scarlet, crimson, yellow, blue, green, purple, golden and brown, will be counted manually and, then, analyzed. The typology of colours is based on Berlin and Kay's (1969) classification. The connotations are judged by analyzing colours in context with special attention to words collocated with CTs. All the colours in the novel have orthophemistic uses; black, grey, red and brown have dysphemistic uses.